If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y*3y=6y
We move all terms to the left:
2y*3y-(6y)=0
We add all the numbers together, and all the variables
-6y+2y*3y=0
Wy multiply elements
6y^2-6y=0
a = 6; b = -6; c = 0;
Δ = b2-4ac
Δ = -62-4·6·0
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{36}=6$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-6}{2*6}=\frac{0}{12} =0 $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+6}{2*6}=\frac{12}{12} =1 $
| 5x+2(x-10,000)=55,000 | | Y+12=15y-4 | | 22=2u-12 | | l=80-1.5 | | 7z-15=6(z+4) | | 3x-1(2+x)=16 | | 39/2=117/n | | 2b−6=4 | | -20.4=5.1x | | -13x=53 | | p=48-3 | | 1-(x)/5=7 | | (3x)+3=3 | | 30+53.45x=60.75 | | 12y-18=7y+22 | | 1-(-3x)=5 | | 5x+19=180 | | 4/x+4=7/x+1 | | 6-3y=-9=2y | | 2/3x+4=-6-4 | | m=3+100 | | 9-(2x)=5 | | m=100+3 | | 7p+17=17 | | (-7x)-2=(-2) | | (5x)-13=(-22) | | m=100-3T | | (-x)-9=(-15) | | −3(y+3)−5(y−2)=14 | | (6+x)/9=3 | | -1/2x-2/5=-3/4 | | x^2+32=-18x |